When an NGO Takes on Public Participation: Preparing a Plan for a Neighborhood in East Jerusalem. (28th September 2012) - Cohen‐Blankshtain, Galit; Ron, Amit; Perez, Alma Gadot
Abstract It is often non‐governmental organizations (NGOs) that promote empowered participation processes, and assume active roles in leading them. However, the ability of NGOs to take on such processes is under‐theorized. In many cases empowered participation involving NGOs takes place without political support from above (or with limited or conditional support). Our goal in this article is to use a case study of participatory planning in East Jerusalem to theorize processes of empowerment in an oppositional political environment. We argue that it is useful to analyze such processes of empowered participation through the concept of power. We describe the process of empowerment as a speculative process in which the NGO has to hedge two mediums of power: it has to build the power of the community to discuss its own goals; and it has to simultaneously manage the transfer of decision‐making power from government bodies to the community.